Environmental Technology Mapping: A Study on Green Patents in Brazil - Menezes, Cláudia Cardinale Nunes (2016)
Currently the Brazilian patent system works as a driver for economic and sustainable development, acting as a type of inductor for innovation of environmental issues. A fact observed in the relationship between green technologies and the patent system is in the form of the Pilot Programme for Green Patents of the National Industrial Property Institute [INPI]. But do green patents developed in Brazil meet the areas of greatest need? And which Brazilian regions do stand out? Using as research the patentometrics method, this article aims to identify the level of utilization of green technologies, using technological mapping of green patents conceded by the INPI. The analysis of research on green patents made it possible to draw a perspective on technology areas, regions and authors who hold green research in Brazil. It was found that the areas with more deferred green patents are directly related to the investments made by the companies in each sector of interest. The identification by region nade South and Southeast atand out, and it is observed that the higher investment in education and scientific and technological infrastructure, the greater the results of development of green research. It is hoped that the paper will contribute to the expansion and understanding of industrial property in the form of green patents.